Eyelid Myoclonia with Absences (Jeavons Syndrome) - J Gordon Millichap (Pediatric Neurology Briefs)
An open-label trial of levetiracetam in 35 patients (23 girls) with eyelid myoclonia (EM) was conducted at the Epilepsy Center, Federico II University, Napoli, and several additional epilepsy centers in Italy.